Impact of Serial Casting on Autonomic Nervous System Responses during Virtual Reality Tasks in Children with Cerebral Palsy: A Pilot Study Comparing Orthoses and Barefoot Conditions - de Paula Paro, Marisa; de Sousa, Raísa Marques; Martinez, Juliana Perez; Simcsik, Amanda Orasmo; Airoldi, Marina Junqueira; Dias, Rodrigo Martins; de Moraes, Íbis Ariana Peña; Magalhães, Fernando Henrique [UNESP]; de Mello Monteiro, Carlos Bandeira; da Silva-Magalhães, Talita Dias (MDPI, 2024)
Cerebral palsy (CP) is a group of movement disorders that impair posture and mobility, often leading to spasticity and joint contractures. Interventions like serial casting are commonly used to improve joint mobility and manage spasticity in children with CP. However, its effects on the autonomic nervous system (ANS) remain unclear. This study aimed to evaluate the effects of serial casting and ankle–foot orthoses (AFOs) on ANS responses during a virtual reality (VR) standing task, comparing these interventions with a barefoot condition. Thirty children with CP were randomized into three groups (n = 10 per group): serial casting, AFOs, and barefoot. Heart rate variability (HRV) was used to assess ANS responses across three phases: seated rest, VR task, and recovery. The results showed that the serial casting group exhibited higher sympathetic activity during rest compared to the other groups, but had a reduced sympathetic response during the VR task. Additionally, the serial casting group displayed a more pronounced parasympathetic rebound during recovery, similar to the orthoses and barefoot groups. While serial casting provides essential joint stability, it alters ANS response patterns, leading to heightened sympathetic activation at rest, without providing significant improvements in ANS behavior during physical activity.
Keywords: autonomic nervous system; cerebral palsy; heart rate; plaster cast; virtual reality